An Interest Group Model of Direct Income Redistribution - Plotnick, Robert D. (The Review of Economics and Statistics, 1986)
An interest group model of the determinants of policies which directly re distribute income to low income persons is developed and tested. The model assum es that altruistic taxpayers, nonaltruistic taxpayers, and needy beneficiaries f orm separate interest groups from which politicians seek support. Benefit levels depend on variables such as taxpayer income and the price of benefits but, unlike median voter models, the model also implies a role for interest group strengt h and competition between political parties. The author uses latent variable met hods and data on the Aid to Families with Dependent Children program to demonstr ate empirical support forthe model. Copyright 1986 by MIT Press.